Chemical Composition and Antimicrobial Activities of the Essential Oils of Viburnum opulus, Viburnum lantana and Viburnum orientala - YILMAZ, NAGIHAN; YAYLI, NURAN; MISIR, GULBIN; COSKUNCELEBI, KAMIL; KARAOGLU, SENGUL; YAYLI, NURETTIN (Asian Journal of Chemistry, 2010)
The composition of the essential oils obtained from the airdried Viburnum opulus and Viburnum lantana were analyzed by GC-MS. 40 and 53 Components were identified in the essential oils and the main component of these taxons were phytol and occidenol in the ratios 7.8 and 6.3 % from V. opulus and V. lantana, respectively. The isolated essential oils of V. opulus, V. lantana and V. orientala were also tested for antimicrobial activity against the bacteria E. coli, K. pneumoniae, P. aeruginosa, E. faecalis, S. aureus, B. cereus and the fungus C. tropicalis, at maximum essential oil concentrations in hexane of 250, 500 and 1000 μg/mL, respectively, though no activity was observed against all the test microorganisms for V. lantana and V. opulus. However, the essential oil of the V. orientale showed weak antibacterial activity against Gram-positive bacteria.